(x-5)^2=(x-3)^2 помогите решить

(x-5)^2=(x-3)^2 помогите решить
Гость
Ответ(ы) на вопрос:
Гость
Вот. решение в фото.....................
Гость
[latex] (x-5)^{2} - (x-3)^{2} = 0[/latex] [latex](x-5-(x-3))*(x-5+x-3)=0[/latex] [latex](x-5-(x-3))*(2x-5-3)=0[/latex] [latex](x-5-(x-3))*(2x-8)=0[/latex] [latex](x-5-x+3)*(2x-8)=0[/latex] [latex](0-5+3)*(2x-8)=0[/latex] [latex](-5+3)*(2x-8)=0[/latex] [latex](-2)*(2x-8)=0[/latex] [latex]-2*2x+2*8=0[/latex] [latex]-4x+2*8=0[/latex] [latex]-4x+16=0[/latex] [latex]-4x=-16[/latex] [latex]x=4[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы